The study of feeding activities and feeding preferences of eight orangutans had been conducted at Schmutzer Primate Centre, Jakarta. The data has been collected from March to September 2008. Data collections of feeding behaviours were performed using focal animal sampling method. While based in 336 hours of observation within 6 months, orangutans spent 53,18% of the time on feeding, 17,27% on resting, and 14,79% on traveling. The daily activity pattern was distributed bimodally with peaks at abo - Ridhatul Zuhra; Dyah Perwitasari- Farajallah; Entang Iskandar (Jurnal Primatologi Indonesia, 2009)
The study of feeding activities and feeding preferences of eight orangutans had been conducted at Schmutzer Primate Centre, Jakarta. The data has been collected from March to September 2008. Data collections of feeding behaviours were performed using focal animal sampling method. While based in 336 hours of observation within 6 months, orangutans spent 53,18% of the time on feeding, 17,27% on resting, and 14,79% on traveling. The daily activity pattern was distributed bimodally with peaks at about 08.00 and 14.00. More feedig took place in the morning (08.00-10.30) and in the afternoon (13.30-16.00), while midday was reserved for resting. Orangutans were fed 96,90% of the feeding time on foods from the Schmutzer Primate Centre, and 3,10% on other foods available in the exhibition cages. Three species of plants were consumed frequently; figs (Ficus benjamina) (0,48%), rumput gajah (Pannisetum purpureum) (0,24%) and velvet tamarind (Dialium indicum) (0,21%), respectively. In addition, orangutans sometimes ate soil, feces, and insects. Key words: Pongo pygmaeus, feeding behavior, Schmutzer Primate Centre